Service innovation through resource integration: An empirical examination of co-created value using telehealth services. (January 2021) - Go Jefferies, Josephine; Bishop, Simon; Hibbert, Sally
Scholars, policymakers and practitioners recognise the potential to improve public services through active citizen involvement and much research has examined the formal opportunities to 'co-produce' changes in the structures and cultures of public services. Yet scholars have devoted little attention to the opportunities for service and social innovation that emerge from the everyday activities of service users and their phenomenological experiences of realising value from service interactions. This qualitative study of telehealth users explores how and why public service beneficiaries co-create value. It argues that understanding citizens' approaches to co-create phenomenological value is a vital component of the collaborative processes that generate social benefit.